BANJIR SUMATERA 2025: REFLEKSI MAQĀṢID SYARĪ‘AH DALAM PENGELOLAAN HUTAN DAN KONSEKUENSI EKONOMI EKSPLOITASI - Hilyati Inayah Siregar; Saparuddin Siregar (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2026)
The 2025 flood disaster in Sumatra represents not only an environmental crisis but also a systemic failure in sustainable forest governance and ethical resource management. This study investigates the root causes of the flood by integrating the Islamic normative framework of Maqāṣid al-Sharī‘ah with contemporary ecological and economic analyses. Through qualitative methods—including normative analysis, policy review, and case comparisons with Malaysia and Morocco—this research demonstrates that deforestation, weak regulatory enforcement, and extractive economic policies have collectively violated key maqāṣid principles, particularly the preservation of life (ḥifẓ al-nafs), wealth (ḥifẓ al-māl), and progeny (ḥifẓ al-nasl). The study further explores the economic consequences of environmental exploitation and evaluates the untapped potential of Islamic financial instruments such as zakat, waqf, and green sukuk in post-disaster rehabilitation and environmental recovery. Findings highlight the urgent need to institutionalize maqāṣid-based governance in Indonesia’s forest and disaster management frameworks. This paper proposes actionable policy recommendations and underscores the role of Islamic ethics in shaping future ecological resilience